The Tradition of Donating Celebrations with the Potangan System in a Review of Sharia Economic Law - Natasya Stifani; Kurniawati, Fitri (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2024)
This research aims to explain in depth the description of sharia economic law regarding the deduction system in the tradition of nyumbang to celebrations in the Ulujami community. This research is library research with a qualitative approach. The data sources used in this research come from various literature journal articles that are relevant to the research topic and describe the facts which are then continued with analysis. The data analysis method used is content analysis of the literature sources used in the research. The tradition of nyumbang in Ulujami shows a strong sense of mutual trust and cooperation between givers and recipients. Trust is a type of trust that people have in each other when interacting with each other in activities based on bonds of brotherhood, mutual giving, and mutual agreement with the aim of producing moral and material benefits for both parties. The Ulujami community has various types of celebrations, including circumcisions, weddings, house building, and even recitation of the Koran. They also carry out a tradition of donating called